The effect of Mesalazine and Nortriptyline on Patients with Irritable Bowel Syndrome with Diarrhea: A Randomized Clinical Trail - Vahedi 1, Hamid; Mousavi 2*, Seyed Abbas; Gholamzadeh 3, Shima; Khosravi 4**, Ahmad (Shahroud Journal of Medical Sciences, 2017)
Background: The objective of this randomized trial was to compare the effects of mesalazine and nortriptyline on relief of abdominal pain, discomfort, abnormal bowel habits and quality of life in patients with diarrhea-predominant irritable bowel syndrome (IBS-D). Methods: In this triple blinded, randomized clinical trial, 44 patients with irritable bowel syndrome with diarrhea were randomly assigned to receive mesalazine (500 mg tablet orally, twice a day) or nortriptyline (10 mg tablet orally, once daily). IBS-D was diagnosed according to the Rome Ⅲ criteria. Before allocation, all patients completed the Beck questionnaire for screening for depression, and the informed consent form. Results: Change score for abdominal pain severity was significantly higher for mesalazine than for nortriptyline (208.5±80.9 V.s 146.8±105.6) and change score for days with pain was not significantly different between two arms (3.9±2.8 V.s 2.8±3.0). The results show that the change score of satisfaction with bowel habits (56.2±20.2 V.s 37.5±24.9) and quality of life (42.0±26.7 V.s 26.3±18.6) in the mesalazine-treated group is greater than in the nortriptyline group.Conclusions: This study showed that mesalazine, as an anti-inflammatory agent for treatment of IBS-D in patients without psychological disorders, is more effective than nortriptyline.